AD, Volume 27, n° 3 & 4, 2002 - Full Issue - Journal System, (Africa Development, 2022)
Contents Introduction. New Public Management: An African Management Reform Paradigm? Dele Olowu ..........................................1 African Case Studies in New Public Management and Its Main Lessons Fashion, Learning and Values in Public Management: Reflections on South African and International Experience Des Gasper ......................................17 Lessons of International and African Perspectives on Public Service Reform: Examples from Five African Countries Gelase Mutahaba & Kithinji Kiragu .....................48 Managing Multiple Modalities of Delivering Basic Services in Ghanaian Cities Nicholas Awortwi ...............................76 Beyond Public Management: African Policy and Management in Response to Globalisation Restructuring the African State for more Effective Management of Globalisation Moses Ν. Kiggundu .............................106 Enhancing the Competitiveness and Productivity of Small and Medium Scale Enterprises (SMEs) in Africa: An Analysis of Differential Roles of National Governments Through Improved Support Services Asmelash Beye ...................................130 Book Reviews Abdel Ghaffar M. Ahmed, 2003, Anthropology in the Sudan: Reflections by a Sudanese Anthropologist. Jay O'Brien .......................................157 Myron Echenberg,2002 Black Death, White Medecine: Bubonic Plague and the Politics Health in Colonial Senegal 1914-1945. Godwin R. Murunga ..................................160 Mamadou Aly Dieng, Les premiers pas de la Fédération des étudiants d'Afrique noire en France (FEANF) (1950 - 1955) de l'union française à Bandoung. Thierno Diop .........................................164